HUBUNGAN USIA, LAMA KERJA ANGKAT-ANGKUT TERHADAP KELELAHAN OTOT TANGAN PADA KULI PANGGUL PADI KENAGARIAN CAMPAGO KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN TAHUN 2025 - Aulia Rahmi Cheni; Nia Watri Wahyuni; Arif Prima; Satrio Bhagas Yudhanto (Ensiklopedia of Journal, 2026)
Manual material handling is still commonly performed by porters (kuli panggul) and may lead to muscle fatigue, particularly during lifting and carrying activities involving heavy loads and prolonged working hours. Muscle fatigue is characterized by decreased muscle strength, slowed movement, and muscle pain or tremors. This study aimed to analyze the relationship between age and working duration and hand muscle fatigue among rice porters in Kenagarian Campago, V Koto Kampung Dalam District, Padang Pariaman Regency, in 2025. This study used an observational design with a cross-sectional approach. The study population consisted of 40 rice porters. Data were collected from January to July 2025 through interviews and hand muscle strength measurements and analyzed using the chi-square test. The results showed that 85.0% of workers were in the high-risk age group, 80.0% had long working durations, and 87.5% experienced high levels of hand muscle fatigue. There was a significant relationship between age (p = 0.018) and working duration (p = 0.046) with hand muscle fatigue. Promotive and preventive efforts, including occupational health education and ergonomic work procedures, are essential to reduce the risk of hand muscle fatigue.Keywords : manual material handling, hand muscle fatigue, porter, age, working duration